The Impact of China's Electricity Deregulation on Coal and Power Industries: Two-stage Game Modeling Approach - HuiHui Liu; ZhongXiang Zhang; ZhanMing Chen; DeSheng Dou (Fondazione Eni Enrico Mattei (FEEM), 2018)
The regulated price mechanism in China's power industry has attracted much criticism because of its incapability to optimize the allocation of resources. To build an “open, orderly, competitive and complete” power market system, the Chinese government launched an unprecedented marketization reform in 2015 to deregulate the electricity price. This paper examines the impact of the electricity price deregulation in the industry level. We first construct two-stage dynamic game models by taking the coal and coal-fired power industries as the players. Using the models, we compare analytically the equilibriums with and without electricity regulation, and examine the changes in electricity price, electricity generation, coal price and coal traded quantity. The theoretical analyses show that there are three intervals of the regulated electricity sales prices which influence the impact of electricity price deregulation. Next, we collect empirical data to estimate the parameters in the game models, and simulate the influence of electricity deregulation on the two industries in terms of market outcome and industrial profitability. Our results suggest that the actual regulated electricity price falls within the medium interval of the theoretical results, which means the price deregulation will result in higher electricity sales price but lower coal price, less coal traded amount and less electricity generation amount. The robustness analysis shows that our results hold with respect to the electricity generation efficiency and price elasticity of electricity demand.
Keywords: Q41; Q43; Q48; L94; L98; 330; China; Electricity; Deregulation; Reform; Coal Industry; Power Industry